STRATEGI GURU DALAM MENANGGULANGI PERUNDUNGAN (BULLYING): STUDI KASUS DI KELAS IV SD NEGERI 70 BANDA ACEH - Hayatun Nisa; Helminsyah; Teuku Mahmud (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Bullying is a common problem in elementary schools that can negatively affect students’ development. This study aims to describe teachers’ strategies in overcoming bullying behavior in the fourth grade of SD Negeri 70 Banda Aceh. This research used a qualitative approach with a case study method. The participants included the classroom teacher, the principal, bullying perpetratos, victims, and witnesses. Data were collected through observation, interviews, and documentation. The findings indicate that bullying in the fourth SD Negeri 70 Banda Aceh occurred in the form of verbal bullying, such as teasing and name-calling, and physical bullying, such as pushing and hitting. The result show that teachers addressed bullying by giving advice and warnings, instilling character values, applying personal approaches to students, and collaborating with the school and parents. These strategies helped recude bullying behavior and create a safe and comfortable learning environment.